Writing revolution : Hispanic anarchism in the United States - Castaneda, Christopher James, 1959-; Feu López, M. Montserrat (University of Illinois Press, 2019)
"Writing Revolution examines the international movement of Spanish-speaking anarchists who sought social and economic freedom in the United States. Scholars from Latin America, Spain, and the United States will trace the nineteenth-century origins of Spanish-language anarchism and explore the manner in which its ideas and practices crossed borders in the Americas and deeply influenced the development of U.S. Spanish-speaking culture and society from the nineteenth through the twentieth century. This is a book that not only explores the evolution and development of anarchist thought and action, it examines how people widely dispersed over time but who had a shared language and perspective on authoritarian regimes found solidarity through communication and work. Transnational Libertad proposes a global approach to U.S. Hispanic anarchist history, culture, and legacy by examining transnational channels and networks, particularly the anarchist press"-- Provided by publisher.
Keywords: Anarchism -- United States -- History.; Press, Anarchist -- United States -- History.; Anarchists -- United States -- History.; Hispanic Americans -- Politics and government.; Hispanic American literature (Spanish) -- History and criticism.; Anarchisme -- États-Unis -- Histoire.; Presse anarchiste -- États-Unis -- Histoire.; Anarchistes -- États-Unis -- Histoire.; Littérature américaine (espagnole) -- Histoire et critique.; SOCIAL SCIENCE -- General.; Anarchism; Anarchists; Hispanic American literature (Spanish); Hispanic Americans -- Politics and government; Press, Anarchist; United States; Criticism, interpretation, etc.; History